The Paradox of Social Ties after the ICT Revolution: A Second-Order Observation - Akahori, Saburo (Journal of Sociocybernetics, 2014)
This paper explores what kinds of distinctions are used when the change of social systems is observed. We seek a more appropriate description of society in the face of online relationships. This task will be carried out through a case study of Japan.  In recent years, the significance of social ties has repeatedly been emphasized in Japan. One example is the frequency of use of the Japanese word kizuna which means “bond”. It sounds odd because conventionally kizuna indicates intimate, continuous relationships, not temporary relationships. Even though the word kizuna means strong ties, now it also implies weak ties. Here we examine the reason why the strange usage of the word kizuna has become acceptable. We focus on topics related to the observation of social ties. On one hand, connections between strangers are becoming more imaginable due to the recent change of communication media after the ICT revolution, especially the rise of so-called social media. On the other hand, social relationships between strangers through social media have been seen as paradoxical in recent years. We assume that this enables us to accept the strange usage of the word kizuna. Then we describe the phenomenon by using other distinctions. For example, we adopt the classic sociological distinction between personal and impersonal. Social relationships between strangers seen in social media can be categorized not as impersonal but as personal; however they are sharply distinguished from social ties in traditional communities or intimate relationships. It can be understood as a variant of “doubling of reality” in Niklas Luhmann’s theory of mass media. This can also be a clue to rethink modernity or to rethink solidarity among heterogeneous people. After the ICT revolution, observations on communications or social ties tend to be paradoxical. However, the recent changes can be seen from the meta-level by using other distinctions. Sociologists have to unfold the paradox and describe them through more appropriate frameworks.